ANALYSIS OF THE FULFILLMENT OF RESTITUTION RIGHTS FOR CHILD VICTIMS OF SEXUAL VIOLENCE CRIME - Mohammad Reza Khatami; Firganefi Firganefi; Malicia Evendia (Law Faculty of Universitas Bandar Lampung, 2023)
Victims of a crime are often children, especially crimes of sexual violence. Sexual violence against children will have a detrimental effect. Impact on health problems and prolonged trauma problems. Children who are victims of criminal acts of sexual violence can cause physical and psychological injuries that must be healed and cared for. The form of legal protection for children who are victims of criminal acts of sexual violence is to provide the right of restitution as the perpetrator's responsibility to fulfill the rights of children who are victims of criminal acts. Decision of the Tanjung Karang High Court No.133/Pid/2021/PT Tjk, convicting the perpetrators of only half of the demands of the Public Prosecutor. This shows that criminal justice in Indonesia is still only focused on giving law to criminals so that the fulfillment of victims' rights cannot be fulfilled optimally. The results of the research show that there are regulations related to restitution but the regulations doesnt guarantee the rights of children as victims because these regulations are unclear in regulating the mechanism for implementing restitution. So that the obstacle is that law enforcement officers are still focused on the basic punishment rather than the rights of victims.